2022
DOI: 10.1371/journal.pone.0272593
|View full text |Cite
|
Sign up to set email alerts
|

Maternal use of acetaminophen during pregnancy and neurobehavioral problems in offspring at 3 years: A prospective cohort study

Abstract: Background Acetaminophen is one of the most commonly used drugs during pregnancy globally. Recent studies have reported associations between prenatal exposure to acetaminophen and neurobehavioral problems in children, including attention-deficit hyperactivity disorders. Little research has investigated these associations in preschool-age children or the potential confounding effects of prenatal stress. The purpose of this study was to examine associations between prenatal acetaminophen exposure and offspring n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
1
6
0
1
Order By: Relevance
“…During pregnancy and breastfeeding periods, woman may use APAP to relieve acute or chronic and it may cause negative consequence to offspring ( Scialli et al, 2010 ). Maternal APAP use during pregnancy is implicated in certain adverse outcomes in offspring, including attention and sleep problems ( Sznajder et al, 2022 ). The cohort studies report that prenatal APAP exposure results in adverse neurodevelopment, including attention-deficit/hyperactivity disorder associated with frontoparietal network brain connectivity ( Ystrom et al, 2017 ).…”
Section: The Effects and Characteristics Of Apap Used In Pregnancymentioning
confidence: 99%
“…During pregnancy and breastfeeding periods, woman may use APAP to relieve acute or chronic and it may cause negative consequence to offspring ( Scialli et al, 2010 ). Maternal APAP use during pregnancy is implicated in certain adverse outcomes in offspring, including attention and sleep problems ( Sznajder et al, 2022 ). The cohort studies report that prenatal APAP exposure results in adverse neurodevelopment, including attention-deficit/hyperactivity disorder associated with frontoparietal network brain connectivity ( Ystrom et al, 2017 ).…”
Section: The Effects and Characteristics Of Apap Used In Pregnancymentioning
confidence: 99%
“…The classes of medicines utilized during pregnancy associated with the development of ASD include antipyretics/painkillers 4,11,13 , antidepressants 12 , antiepileptic drugs 4,8,10 and antibiotics 9,13,14 . This association has been observed when exposure to the drug occurs in the first and second trimesters 14 or second and third trimesters 23 or throughout pregnancy 11 . However, other studies found no association between maternal drug utilization and ASD [24][25][26][27] .…”
Section: Introductionmentioning
confidence: 95%
“…A saúde mental das mulheres durante a gestação também é uma área de preocupação A depressão e a ansiedade são as condições mais comuns, de maior prevalência, como demonstrado por estudos da literatura (FARREN et al, 2022;TAMIRU et al, 2022;RUNKLE et al, 2023). A presença desses transtornos pode ter consequências negativas para a saúde da mãe e do feto, incluindo um aumento do risco de parto prematuro, baixo peso ao nascer, desmame precoce e um maior risco de problemas comportamentais e emocionais na criança (SZNAJDER et al, 2022). Além disso, a saúde mental das mães também pode ser afetada após o parto e, algumas puérperas podem desenvolver depressão, que é um transtorno depressivo maior, com impacto significativo e duradouro, na mãe e no bebê (INEKWE;LEE, 2022).…”
Section: Introductionunclassified